STUDI PENGOLAHAN LIMBAH CAIR PENYAMAKAN KULITDI PT BUDI MAKMUR KECAMATAN GEDONG KUNING YOGYAKARTA TAHUN 2014 - Sri Rejeki Indah Astiani; Djamaluddin Ramelan (Buletin Keslingmas, 2015)
PT Budi Makmur is one of the made leather industry that located in Yogyakarta. It processing a raw leather which from goat leather that processed into wolves, shoes, etc. PT Budi Makmur also produce water waste that flows to the river and if the waste is not produced in the right way, the waste will be very dangerous for the ecosystem in that river.The aim of this research are to know the process of the liquid waste producing leather tanning, the parameter of the liquid waste before and after through the producing process (COD, BOD, TSS dan pH) , and the condition of the liquid waste producing leather tanning.The kind of this research is descriptive. The research done by collecting the field data an laboratorium, and then analyzed and compared with the existing theory and quality of the liquid waste producing leather tanning.The result show that the source of the waste produce from the leather tranning. Liquid waste that produced is about 8.000-12.000 gallon per 1.000 wet leather pond that produced. The quality of the influent is BOD 1.946mg/lt, COD 1965mg/lt, TSS 1.774mg/ltd and pH 7.50. The quality of the effluent is BOD 98.61mg/lt, COD 100mg/lt, TSS 1130mg/lt and pH 7,49. The step of the liquid waste processing are: filtering ink, equalitation ink, sedimentation, aeration and active mud.The writer conclude that PT Budi Makmur has already optimal to decrease the content that contained in the leather-liquid waste producing but the effluent that is produced still exceed the exsisting standart quality. The suggestion to PT Budi Makmur is to more care about the liquid waste producing.